Analisis Kesalahan Penggunaan Ejaan Bahasa Indonesia Pada Tugas CJR Biologi Sel Mahasiswa Universitas Negeri Medan Kelas PSPB 2022 B - Amanda Giovani; Dita Zahara Gultom; Gabriella Munthe; Khairina Hafiza Pasaribu; Lili Tansliova (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
PSPB 2022 B students are categorized as still not being careful in using spelling in report writing. This research method is a qualitative method with data collection techniques in the form of a literature study of the CJR Cell Biology PSPB 2022 B report. The results of this research show that each group has errors related to the use of language spelling. Research conclusions regarding errors in using the order of writing a sentence, including the use of capital letters and punctuation that do not comply with EBI.